(untitled) (Research, Society and Development, 2022)
The main purpose of biofortification is to increase the nutritional value of specific staple foods. Some researchers argue that biofortification is an important strategy to combat malnutrition and hidden hunger. Others, however, criticize it massively, pointing it out as a technique that does not promote human nutrition or food security. These divergences regarding the use of biotechnology and the use of genetic engineering in food production is one of the main controversies that have been debated in contemporary times. Therefore, the objective of the present study was to prepare a literature review to discuss the positive and negative aspects of food biofortification. For the development of investigations, research in digital libraries was used as a methodology, with the descriptors "biofortification", "nutrition", "hidden hunger", "food security", resulting in 48 works, being read and analyzed their results. respective abstracts and introductions, selected for discussion 27 scientific productions, published in the last 20 years in Portuguese. At the end of the research, it was concluded that food biofortification, despite having several positive attributes, is a complementary strategy to other interventions already in place and that it must be inserted in a context that contemplates an integrated food system, since malnutrition , hidden hunger and food and nutrition security are directly related to socio-political and socio-environmental issues.